Penggunaan Media Pembelajaran Alat Peraga Torso Ikan untuk Meningkatkan Hasil Belajar Siswa - Rahma Atillah; Yulda, Yulda; Ahmad Satibi (DIAJAR: Jurnal Pendidikan dan Pembelajaran, 2024)
Fish torso props are learning media that can be used to understand the subject about fish morphology and anatomy. The subject is one of the difficulties for students because students' understanding of the concept of the subject is still relatively low. Therefore, the aim of this study is to determine the effect of fish torso tool and the magnitude of the influence they have on student learning outcomes. This study used a quantitative approach with a quasi-experimental method. The samples used in this research were grade X students of the Freshwater Fisheries Agribusiness skills program at SMKN 1 Warunggunung which consisted of two classes that is class X APAT 1 as the control class and class X APAT 2 as the experimental class. The control class will apply learning using Powerpoint media while the experimental class will apply learning using fish torso tool as media. Moreover, the data collection methods used were tests in the form of pretests and posttests, as well as non-tests in the form of observation and documentation. The research results show that the average N-gain scores in the experimental class is 68% while in the control class it was 37%. Therefore, it shows that the fish torso tool has an influence on student learning outcomes. The magnitude of this influence is proven through the effect size test which obtained a value of 1.865. Thus, it can be concluded that the fish torso tools have quite an effective effect on student learning outcomes.